Evaluasi Kurikulum dan Pembelajaran Pendidikan Agama Islam di Era Digital: Perspektif Pendidikan Islam - Kasmila, Amia; Hadiati, Eti; Rizqi, Diah Irdiyana; Septuri, Septuri; Fauzan, Ahmad (Universitas Muhammadiyah Magelang, 2025)
The digital era demands a comprehensive transformation in the educational system, including in the subject of Islamic Religious Education (PAI). This article aims to evaluate the curriculum and instructional practices of PAI within the context of the digital era from an Islamic education perspective, focusing on: (1) the adaptation of the PAI curriculum to digital learning needs, (2) technology-based PAI learning practices, and (3) the main challenges and recommendations for improvement. The research employs a qualitative-descriptive approach through library research, analyzing scientific publications, educational regulations, and recent literature from the past four years. The findings reveal that although the PAI curriculum has begun to incorporate digital components and online learning media, several implementation gaps remain, such as limited digital literacy among teachers, unequal access to technology, and insufficient systematic integration of Islamic values within digital learning platforms. Technology-based PAI learning has proven effective in enhancing student motivation and accessibility; however, challenges related to access disparity, moral development, and character formation remain significant. The study concludes that the evaluation of the PAI curriculum and learning in the digital era must emphasize synergy between technology and Islamic values, ensuring that digitalization not only modernizes learning but also strengthens students’ spiritual, moral, and Islamic character. The study recommends improving teachers’ digital competencies, ensuring equitable technological infrastructure, developing digital learning media explicitly infused with Islamic values, and formulating evaluation models responsive to both digital contexts and Islamic educational principlesThe digital era demands a comprehensive transformation in the educational system, including in the subject of Islamic Religious Education (PAI). This article aims to evaluate the curriculum and instructional practices of PAI within the context of the digital era from an Islamic education perspective, focusing on: (1) the adaptation of the PAI curriculum to digital learning needs, (2) technology-based PAI learning practices, and (3) the main challenges and recommendations for improvement. The research employs a qualitative-descriptive approach through library research, analyzing scientific publications, educational regulations, and recent literature from the past four years. The findings reveal that although the PAI curriculum has begun to incorporate digital components and online learning media, several implementation gaps remain, such as limited digital literacy among teachers, unequal access to technology, and insufficient systematic integration of Islamic values within digital learning platforms. Technology-based PAI learning has proven effective in enhancing student motivation and accessibility; however, challenges related to access disparity, moral development, and character formation remain significant. The study concludes that the evaluation of the PAI curriculum and learning in the digital era must emphasize synergy between technology and Islamic values, ensuring that digitalization not only modernizes learning but also strengthens students’ spiritual, moral, and Islamic character. The study recommends improving teachers’ digital competencies, ensuring equitable technological infrastructure, developing digital learning media explicitly infused with Islamic values, and formulating evaluation models responsive to both digital contexts and Islamic educational principles.